Experimental studying the effect of water temperature on friction properties of marine propeller sliding bearing - Trinh, Hiep Xuan; Nguyen, Ngoc Bich; Nguyen, Sinh Truong (Vietnam Journal of Mechanics, 2021)
This paper presents the effect of water’s temperature on the friction properties of materials used in marine propeller sliding bearing. Copper-Rubber and Copper-Capron, two common pairs of material in the shaft water-lubricated polymer bearing were chosen to conduct experiments with the pin-on-disc model. Various conditions including water temperature, stress, and sliding velocity were examined, their results showed that in the range 30 °C to 100 °C of water temperature, the frictional coefficient of both friction pairs were unchanged under the small stress and low sliding velocity (0.3 MPa and 0.9 m/s). While in the case of stress and sliding velocity were both high (0.6 MPa and 1.5 m/s), it increased significantly in a certain transition temperature range. This temperature range of the pair Copper-Rubber and Copper-Capron is 50 °C to 60 °C and 80 °C to 90 °C, respectively. The experiment’s results also pointed out that in these transition temperature ranges, the friction coefficient of two pairs was slightly influenced by the change in sliding velocity, whereas the stress change has an important impact on its values. Nonetheless, when the water temperature was below the transition range, the effect of the stress change on the friction coefficient was not significant. Thus, high water temperature is the main reason for the friction coefficient’s increase rather than the increase of the stress. This work is expected to broaden the understanding of the friction behavior of the water-lubricated polymer bearing.